TAWHID EDUCATION IN BEIJING'S ASSALAMU'ALAIKUM NOVEL BY ASMA NADIA - Syafi’ie, Imam (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
The purpose of this study was to describe (1) the structure of the Assalamualaikum Beijing novel by Asma Nadia (2) the religious values of the Assalamualaikum Beijing novel by Asma Nadia (3) the relevance of the religious value of the Assalamualaikum Beijing novel by Asma Nadia . This study used descriptive qualitative method. Data collection techniques are library techniques, see notes, and interviews. The source of the data in the study is the novel Assalamualaikum Beijing by Asma Nadia. The validity of the data uses source and theory triangulation. The analysis technique is to reduce data and present data. Data analysis can be summarized as follows. First, this novel contains story facts and themes about migration as a process of finding true love. Second, the religious value of the novel is divided into three elements, namely, (1) aqeedah, (2) morality, and (3) sharia. Third, the results of the analysis of Beijing's Assalamualikum religious values by Asma Nadia are relevant as teaching materials in high school based on core competencies and basic competencies of class XI in KD. 3.11 analyzes messages from one fiction book that is read. There are three aspects of teaching material criteria in the study: aspects of language, aspects of psychology, and aspects of cultural background